Multicultural Education as a Strategy to Strengthen Tolerance and National Character: The Role of Policy, Implementation, and The Challenges of Digital Globalization - Sherly Lisfitriani; Nanda Jaka Putra Pratama; Derna Wati; Silvi Yulia Tantri; Asniti Karni; Dayun Riyadi (Journal of Social Work and Science Education, 2026)
Multicultural education has a strategic role in shaping the character of a nation that is tolerant, inclusive, and able to live in harmony in the midst of the diversity that exists in Indonesia. This research aims to analyze how multicultural education can be optimized through three main aspects: the role of policies and curriculum, implementation practices in boarding schools, and the challenges of digital technology globalization. This research method uses a literature study approach, data is collected through books, journal articles, policy documents, and academic publication data. Data was analyzed using content analysis techniques by examining various scientific sources relevant to education policies, multicultural implementation models, and digital social dynamics in society. The results of the study show that national policies and curricula play an important role as a foundation for integrating multicultural values, while schools and Islamic boarding schools are the main focus in getting used to the values of tolerance and learning practices. However, the era of digital globalization has created new challenges that can threaten the formation of a tolerant character of students. Therefore, strengthening multicultural education needs to be accompanied by critical digital literacy and collaboration between institutions to be able to create an educational ecosystem that is adaptive to the times. This research emphasizes that multicultural education that is integrated with educational policies, practices, and digital literacy is an effective strategy in strengthening the nation's character in the global and digital era.